Avaliação do extrato etanólico das folhas de Eugenia uniflora L. (Myrtaceae) sobre a expressão dos genes C3, CAT, GPx e BDNF em um modelo animal de neurodegeneração - Lira, Gilvana Scoculi de (2018)
AD is a progressive neurodegenerative disorder that manifests itself through the global cognitive decline, mainly on memory functions. The damages associated with AD are related to cellular lesions from oxidative damage and neuroinflammation. Considering that AD is an uncured disease yet, the search for alternative therapies that act to reduce the damages associated with this disease can improve patients’ quality of life. Therefore, this study aimed to evaluate the neuroprotective potential of the ethanolic extract leaves of E. uniflora L. in an animal model of neurodegeneration associated with AD, through the expression analysis of four genes associated with neurogenesis and synaptic plasticity - brain derived neurotrophic factor (BDNF), inflammation – C3 and oxidative stress - glutathione peroxidase (GPx) and catalase (CAT). Eighteen male Wistar rats were divided into four groups. Group 1 received icv citrate buffer and 10% of ethanol v.o; group 2 (n = 5) received icv administration of STZ (3 mg / Kg) and 10% of ethanol v.o; group 3 (n = 5) and group 4 (n = 4) received icv administration of STZ and were treated with ethanolic extract of E. uniflora L. v.o at concentrations of 300 mg / Kg and 1000 mg/ Kg, respectively. Treatement with the extract was performed for one month after the icv injection of STZ. After three months of the end of treatement, the animals were euthanized. Total hippocampal RNA was extracted using TRIzolTM Reagent in combination with the PureLink® RNA Mini Kit. The RNA samples were converted to cDNA using the GoScripTM Reverse Transcriptase kit. Expression analysis of the BDNF, C3, GPx and CAT genes was performed by the RT-qPCR techinique. Data were analyzed using the comparative Ct (Threshold cycle) method to determinate relative levels of mRNA expression. Relative quantification values were submitted to ANOVA. The results showed that there was no significant difference in the relative expression of the studied genes in the analyzed groups. Although these genes are reported to be strong candidates for AD, the results found in the present study demonstrated that icv injection of STZ does not lead to altered expression of BDNF, C3, GPx and CAT genes within four months afterwards administration of STZ. In addition, the treatement with ethanolic extract of E. uniflora L. v.o does not changes the expression of these genes three months after the end of the treatment.